Murilo Chevalier e o Babado Processual: um corpo/corpa em performance na rede - Dias, Wagner Miranda (Farol, 2022)
The article investigates aspects of performer Murilo Chevalier’s creative process. The reflection is structured in the observation of his performative writing and in the analysis of his profile on Instagram in the pandemic context. The importance of transits that incorporate, to their creative path, processes of interlanguage translation and questions about heteronormativity and censorship of bodies is highlighted. The theoretical foundation takes place in dialogue with Cecilia Almeida Salles, Edgar Morin, Josette Fèral and Jacó Glusberg, among others.